Pijat I Love You (ILU) Solusi Asuhan Kebidanan dalam Mengatasi Bayi Kembung - Zulhendri, Annisa Fitri Nadillah; Lita Nafratilova (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
The need for continuous midwifery care (Continuity of Care) is crucial given the high maternal and infant mortality rates that still frequently occur. One common problem in neonates is flatulence, which can cause discomfort to the baby and anxiety to parents. One non-pharmacological treatment that has been proven effective for flatulence in infants is the "I Love You" (ILU) massage technique. This technique has been widely recognized for its simplicity and safety in providing comfort to infants experiencing flatulence. This study aims to explore the effectiveness of the ILU massage technique on an 11-day-old infant experiencing flatulence symptoms. The research design used was a descriptive case study, in which Mrs. Q's baby, who complained of flatulence, was the subject of the study. The ILU massage technique consisted of movements that form the letters I, L, and U on the infant's abdominal area, which aims to stimulate gas movement in the digestive tract. In addition to the ILU massage technique, the intervention also included other supporting movements such as the moon-sun movement and flexing the infant's legs to increase the effectiveness of gas expulsion. The results of this intervention showed a positive response from the infant, with the infant beginning to pass gas after the massage. This suggests that therapy using the ILU massage technique can reduce the symptoms of bloating in infants. Furthermore, mothers were educated on proper breastfeeding positions to prevent air intake, which can exacerbate bloating. Mothers were also taught how to perform ILU massage independently at home, enabling parents to be more active in their infant's care.